Clinicopathological Profile of Rhabdomyosarcoma in Children (Journal of Bangladesh College of Physicians and Surgeons, 2012)
Objectives: To describe the clinical profile as well as  histopathological sub-types of Rhabdomyosarcoma in  children.Methods: A hospital base prospective observational study  was conducted among 20 diagnosed cases of  Rhabdomyosarcoma in children, those attending in  Hemato-Oncology department of Bangabandhu Sheikh  Mujib Medical University (BSMMU), Dhaka in the period  between January to December 2009.Results: The peak incidence of Rhabdomyosarcoma was  in 1-5 years of age group (n=9, 45%) with mean age 6.83  years with male to female ratio 5.66:1. The common sites  of primary tumor was in head and neck region (40%, n=08),  followed by genito-urinary tract, 30% (n=06), extremities  20% (n=04), trunk 10% (n=02). The most common clinical  presentation was mass lesion 100% (n=20), followed by local  pain 25% (n=05), urinary obstructions 15% (n=03)  dysphagia, chronic otorrhea, dysuria, haematuria, and  proptoses were 10% each (n=02, each); The histological  sub-types were Embryonal 60% (n=12), alveolar 30% (n=6),  and Botryoid 10% (n=02); Of Embryonal variety in head  and neck region 58.33% (n=7), and Genito-urinary sites  41.67% (n=5); of Alveolar variety in trunk 66.67% (n=4),  and in extremities33.33% (n=2), of Botryoid sub-type  frequency was equal in head - neck region and genitourinary  site 50% each (n=1).Conclusion: Children with Rhabdomyosarcoma presented mostly in 1 to 5 years of age, with mass lesion (100%),  predominantly in head and neck region (40%) and the  commonest histological sub-type was Embryonal variety  (60%). DOI: http://dx.doi.org/10.3329/jbcps.v30i3.12461 J Bangladesh Coll Phys Surg 2012; 30: 132-136